2022
DOI: 10.3390/ijerph192315859
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Vascular Endothelium and Angiogenesis by Blood-Flow-Restricted Exercise

Abstract: Blood-flow-restricted exercise (BFRE) has been gaining constantly increasing interest in rehabilitation, but its influence on endothelial functions has not been well studied yet. Our aim is to examine the influence of low-resistance BFRE on endothelial functions and angiogenesis. This prospective cross-over study involved 35 young healthy adults. They conducted a 21-min low-resistant exercise with blood flow restricted by pressure cuffs placed on arms and tights. They also did the same training but without blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The studies were carried out in 12 countries, mainly in the USA ( n = 13) and Brazil ( n = 8) from 2005 [ 27 ] until 2022 [ 28 ]. Most studies used a crossover ( n = 21) or RCT ( n = 13) design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were carried out in 12 countries, mainly in the USA ( n = 13) and Brazil ( n = 8) from 2005 [ 27 ] until 2022 [ 28 ]. Most studies used a crossover ( n = 21) or RCT ( n = 13) design.…”
Section: Resultsmentioning
confidence: 99%
“…• AI: Four studies were identified [43][44][45][46], but only Amorim et al showed a more decisive influence of BFR over non-BFR exercise [43]. • AI75: None of the three identified studies reported any significance in the change in AI75 between BFR and non-BFR exercise [28,43,45].…”
Section: Vascular Stiffness Parametersmentioning
confidence: 99%
“…The possible effect mechanism of LIRT + BFR to improve walking is that the increased muscle strength in the older adults improves the control of the joints of the lower limbs, which in turn maintains gait stability [ 33 , 34 ]. LIRT + BFR stimulates angiogenesis (increased serum concentrations of PECAM-1, CD34, VEGF-R2) and improves endothelial function (increased Flow-Mediated Dilatation (FMD)), thereby improving muscle function and walking distance [ 16 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in muscle mass and strength could improve muscle function [ 15 ]. Moreover, LIRT + BFR stimulates angiogenesis and enhances endothelial function, which in turn improves muscle function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it seems that BFRT and its role in vasodilatory regulation and influence on endothelial functions is very important and is of particular research interest. Low intensity BFRT is more efficient in the stimulation of angiogenesis compared to the same training performed without blood flow restriction (BFR) [27]. Horiuchi et.…”
Section: Introductionmentioning
confidence: 99%